1980
DOI: 10.1002/art.1780230807
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of prostaglandin e production by bacterial endotoxins in cultured human synovial fibroblasts

Abstract: E coli, shigella, salmonella, and cholera endotoxins stimulated prostaglandin E (PGE) production by cultured human synovial and foreskin fibroblasts. The minimal effective dose of Shigella endotoxin was 2 pg/ ml and a maximal response was observed at 10 pg/ml. PGE stimulation was first detected 7 hours after addition of cholera endotoxin. Stimulation by shigella endotoxin of both PGE and hyaluronic acid production was inhibited by indomethacin and aspirin. The present results suggest that PGE is a mediator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 24 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…It did not stimulate prostaglandin E2 (PGE2) by monolayer cultures of rabbit synoviocytes. LPS from several gram-negative organisms stimulate PGE2 (20), and we have confirmed this finding in unpublished studies (R. J. Rothenberg and K. Takayama). Moreover, fraction E had a higher Rf value than the standard value for monophosphoryl lipid A.…”
supporting
confidence: 85%
“…It did not stimulate prostaglandin E2 (PGE2) by monolayer cultures of rabbit synoviocytes. LPS from several gram-negative organisms stimulate PGE2 (20), and we have confirmed this finding in unpublished studies (R. J. Rothenberg and K. Takayama). Moreover, fraction E had a higher Rf value than the standard value for monophosphoryl lipid A.…”
supporting
confidence: 85%
“…Recently, Yaron et al. (17) Lipopolysaccharides Induce Cartilage Degradation . 2017 demonstrated that bacterial endotoxins could stimulate prostaglandin E production by synovial and foreskin fibroblasts.…”
Section: Resultsmentioning
confidence: 99%